2020
DOI: 10.3389/fonc.2020.562147
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Oral Meglumine Diatrizoate Esophagogram in Screening for Esophageal Fistula During Radiotherapy or Chemoradiotherapy for Esophageal Cancer

Abstract: Background: This study aimed to investigate the specificity and sensitivity of oral meglumine diatrizoate esophagogram in screening for esophageal fistula during radiotherapy or chemoradiotherapy for esophageal cancer and determine if early detection and intervention could improve the prognosis of esophageal fistulas. Methods: Esophageal cancer patients undergoing radiotherapy or chemoradiotherapy were included. Weekly oral meglumine diatrizoate esophagograms were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thirdly, half of the patients included in the study were staged as T4b by CT imaging and not by endoscopy. Furthermore, even though the esophagography and CT can be the alternative approaches to diagnose esophageal fistula formation, pre-treatment fistula could still not be fully excluded when endoscopy was not feasible in these patients with serious stenosis [28,29]. Despite these limitations, we consider that our study is the basis for developing clear selection criteria for the subgroup of T4b patients who would benefit from CRT and not develop fistula.…”
Section: Discussionmentioning
confidence: 97%
“…Thirdly, half of the patients included in the study were staged as T4b by CT imaging and not by endoscopy. Furthermore, even though the esophagography and CT can be the alternative approaches to diagnose esophageal fistula formation, pre-treatment fistula could still not be fully excluded when endoscopy was not feasible in these patients with serious stenosis [28,29]. Despite these limitations, we consider that our study is the basis for developing clear selection criteria for the subgroup of T4b patients who would benefit from CRT and not develop fistula.…”
Section: Discussionmentioning
confidence: 97%
“…Most surgeons are concerned about barium extravasation into the thorax [22,23]. A recent study showed that oral meglumine diatrizoate esophagography using CT has a high sensitivity of 100% and a specificity of 98.9% in esophageal fistula screening [24]. However, in 20% of cases, the fistula could not be identified by preoperative CT.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons are concerned about barium extravasation into the thorax [21,22] . A recent study showed that oral meglumine diatrizoate esophagography using CT has a high sensitivity of 100% and a speci city of 98.9% in esophageal stula screening [23] .However, in 20% of cases, the stula could not be identi ed by preoperative CT. Indeed, water-soluble contrast agents are hyperosmolar and could draw uid into the lungs, causing pulmonary edema in case of aspiration into the tracheobronchial tree [21] .…”
Section: Discussionmentioning
confidence: 99%